Burnout syndrome in informal caregivers of older adults with dementia: A systematic review - Alves,Ludmyla Caroline de Souza (2019)
ABSTRACT Dementia is a constant concern for the public health system. Also, it impacts family members who provide informal care, often culminating in overload due to the emotional stress and physical distress of caregivers. Objective: This systematic review aimed to identify the consequences of Burnout Syndrome in informal caregivers of older adults with dementia. Methods: The search was performed spanning the last 10 years, in English, Portuguese or Spanish. The databases used were PubMed, SciELO, Web of Science and LILACS. The descriptors were obtained from MeSH and DeCS, which were, “caregivers”, “burnout”, “aged”, “psychological stress” and “dementia”. The selected articles included studies conducted with informal caregivers of community-dwelling older adults diagnosed with any type of dementia. The excluded articles had the following characteristics: the participants were not informal caregivers, the older adults were not diagnosed with dementia, or the main theme was not related to the Burnout Syndrome. Results: Initially, 1,208 articles were found. One hundred and forty-six were eliminated because they were duplicates. A further 1,033 were excluded because they did not meet the inclusion criteria. Twenty-nine studies were selected for full reading and 22 were excluded, giving 7 studies for inclusion in this review. Conclusion: The results showed that the Burnout Syndrome negatively affected caregivers’ quality of life and was associated with patient depressive and anxious symptoms and abusive behavior by caregiver. There is a need for studies with interventions addressing this issue.